Dinamika Program dan Kebijakan Peningkatan Produksi Padi - Sri Wahyuni; Kurnia Suci Indraningsih (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2003)
EnglishRice Production Enhancement Programs (P4) is consistently carried out by the government to meet domestic demand for rice. This paper describes dynamics of P4 implementation, namely their strengths and weaknesses. There were 11 programs launched, beginning with Central Rice Program (Padi Sentra) in 1958 up to Special Intensification (Insus) in 1979 with highest achievement of rice self sufficiency in 1984. Insus was improved in 1987 and it was then called as Supra Insus. In 1990 rice production was stagnant and rice import tended to enlarge. Rice Based Farming System with Agribusiness Orientation (SUTPA), Agribusiness Oriented Intensification (Inbis), and Self Reliance Movement on Rice, Corn, and Soybean (Gema Palagung) programs were introduced to anticipate changing domestic and international circumstances. El Nino took place when the programs were carried out triggering delay of harvest seasons and low production. At last, paradigm of agricultural development was improved through system development and agribusiness oriented, namely corporate farming as the starting point of on-going Integrated Crops and Resources Management (PTT) program. To induce the farmers nationwide to adopt technologies immediately the government copes with many constraints. It is suggested that the generated technologies are packed in sociodrama before disseminated intensively through various mass media, especially television.IndonesianUntuk mencukupi kebutuhan beras, pemerintah terus mengupayakan program peningkatan produksi padi (P4) melalui berbagai kebijakan. Tulisan ini mengemukakan dinamika P4 yang telah diimplementasikan dengan menganalisis kelemahan dan kekuatan suatu program. Tujuan penulisan untuk memperoleh opsi kebijakan P4 mendatang. Ada sebelas program yang telah diluncurkan, diawali dengan Program Padi Sentra (1958) hingga lahir Intensivikasi Khusus (1979) yang berhasil meraih swasembada beras (1984). Tahun 1987 Insus disempurnakan menjadi Supra Insus. Tahun 1990 produksi padi cenderung stagnan, import beras terus meningkat. Untuk merespon berbagai perubahan lingkungan internasional dan domesik diimplementasikan program Sistem Usahatani Berbasis Padi Berorientasi Agribisnis (SUTPA), Intensifikasi yang Berwawasan Agribisnis (Inbis) dan Gema Palagung. Saat program dalam implementasi terjadi El-Nino yang menyebabkan panen mundur dan produksi rendah. Akhirnya dilakukan pembenahan paradigma dalam pengembangan pertanian yaitu mutlak berbasis pengembangan sistem dan berorientasi agribisnis, yaitu usahatani korporasi yang selanjutnya menjadi dasar dalam program Pengelolaan Tanaman dan Sumberdaya Terpadu (PTT) yang sedang diuji. Selalu ditemukan kendala dalam menyebarluaskan teknologi yang telah dihasilkan dalam skala luas agar cepat diadopsi petani. Diusulkan agar teknologi yang telah dihasilkan dikemas dalam sosiodrama kemudian disebarluaskan secara intensif melalui berbagai media terutama televisi.